DEEP-WATER EXPLORATORY BOTTOM LONG LINING IN THE WATERS OF THE ARAFURA SEA - Badrudin Badrudin; Ngurah N. Wiadnyana; Berbudi Wibowo (Indonesian Fisheries Research Journal, 2005)
Bottom long line fisheries in the continental shelf area of the Arafura Sea has have practised and developed since the last two decades. But bottom long lining in the slope area seemed to be unusual fishing operation for most Indonesian fishers as this fishing activily facing a relatively higher rbks of fishing gear lost.